Experience in endoscopic treatment of cystic formations of the esophagus and mediastinum - Ya. V. Ruchkina; A. A. Smirnov; M. M. Saadulaeva; E. V. Blinov; A. Yu. Korolkov; S. F. Bagnenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The objective was to evaluate the safety and effectiveness of endoscopic methods for removing cystic formations of the esophagus and mediastinum.Methods and materials. The study included 17 patients with esophageal and mediastinal cysts. All patients underwent gastroscopy, endoscopic ultrasonography and computed tomography at the diagnostic stage to determine the localization, sizes and topography of the formation.Results. In all cases, the formations were successfully removed. Submucosal tunnel endoscopic resection (STER) was successfully performed in 14 patients, the average operation time was 126 minutes. In 3 patients, the formations were removed by endoscopic submucosal dissection (ESD), the average operation time was 55 minutes. Two patients in the postoperative period had esophageal diverticulum in the area of previously removed formations.Conclusion. Submucosal tunnel endoscopic resection is safe and effective in the treatment of cystic formations of the esophagus and mediastinum. Long-term results of STER require further study.